Benefits of Yoga in Sports: Enhancing Physical and Mental Well-being through Yoga in Sports (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An ancient practice that originated in India. This practice integrates mind, body, and spirit to promote health and well-being.What is yoga is the question which comes to mind for anybody thinking of starting yoga. Yoga is an ancient system developed over the centuries by the Sages of India. Yoga is a system of training of mind, body and spirit for purification of soul and attaining oneness with the supreme consciousness. The goal of yoga is to calm the mind, ensure better co-ordination of mind and body so that we live a healthy life and experience spiritual growth. Regular practices of asana maintain the physical body in an optimum condition and promote health even in an unhealthy body. Through asana practice, the dormant energy potential is released and experienced as increased confidence in all areas of life, yogasna have in the development of the physical, mental, and spiritual personality, whereas pure exercise only has physical effect on muscles and bones Physical exercises are performed quickly and with a lot of heavy breathing, yogasana are performed slowly with relaxation and concentration. The benefits of various yoga techniques have been professed to improve body muscular strength, performance, stress reduction, attainment of inner peace and self-realization Schools are dynamic setting for promoting health and wellness through various or related areas such as physical education and sports.